2022
DOI: 10.3233/npm-210793
|View full text |Cite
|
Sign up to set email alerts
|

Massive perinatal left ventricle infarction treated with tissue plasminogen activator: No ECMO – A case report

Abstract: Neonatal myocardial infarction due to coronary thrombus is a rare cause of acute heart failure and is associated with high morbidity and mortality. We present a rare case of a full-term newborn who developed coronary artery thrombus treated with intracoronary recombinant tissue plasminogen activator infusion while undergoing therapeutic hypothermia. Also, we describe a unique treatment strategy to support systemic circulation sparing the patient from neonatal extracorporeal membrane oxygenation and its complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The tPA is a fibrinolytic agent. It has been used in the treatment of systemic and ocular conditions such as acute myocardial infarction, post-cataract, or vitrectomy fibrin reaction ( 11 , 12 ). In animal experimental models, it was shown that up to 50 μg/mL tPA administered to subretinal space is not toxic ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tPA is a fibrinolytic agent. It has been used in the treatment of systemic and ocular conditions such as acute myocardial infarction, post-cataract, or vitrectomy fibrin reaction ( 11 , 12 ). In animal experimental models, it was shown that up to 50 μg/mL tPA administered to subretinal space is not toxic ( 13 ).…”
Section: Discussionmentioning
confidence: 99%